The gradual - Priest, Christopher 1943-2024 (Gollancz, 2017)
In the latest novel from one of the UK's greatest writers we return to the Dream Archipelago, a string of islands that no one can map or explain. Alesandro Sussken is a composer, and we see his life as he grows up in a fascist state constantly at war with another equally faceless opponent. His brother is sent off to fight; his family is destroyed by grief. Occasionally Alesandro catches glimpses of islands in the far distance from the shore, and they feed into his music - music for which he is feted. But all knowledge of the other islands is forbidden by the junta, until he is unexpectedly sent on a cultural tour. And what he discovers on his journey will change his perceptions of his country, his music and the ways of the islands themselves. Playing with the lot of the creative mind, the rigours of living under war and the nature of time itself, this is Christopher Priest at his absolute best